Supply chain management: managing price inflation - Prokop, Darren (Henry Stewart Talks, 2023)
Disinflation, Deflation, Employee wages, Consumer Price Index (CPI), Producer Price Index (PPI), Central and commercial banks, The COVID-19 pandemic, Concerns of inflation, Supply lines, US federal government